Pengaruh Pembiayaan Murabahah Terhadap Return On Assets (Roa) Pt. Bank Syariah Mandiri - Eunike Petrina Damai Sejati Halawa (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2023)
The purpose of this study is: To explain the magnitude of the Effect of Murabahah Financing on ReturnOn Assets (ROA) of PT. Bank Syariah Mandiri in 2017-2020. The type of research used in this study isquantitative research, namely research that uses data analysis in the form of numeric/numbers frommonthly financial reports that have been published by PT. Mandiri Syariah Bank. Based on the resultsof the data analysis carried out, it can be seen how the influence of murabahah financing has on theprofitability level of Return On Assets (ROA) at Bank Syariah Mandiri for the period 2017 – 2020 withthe following conclusions: